Kreativitas dan Inisiatif Guru dalam Pengembanggan Mutu Pembelajaran Online - Ibnu Asakir; Fitri Mahmudah (Jurnal Studi Guru dan Pembelajaran, 2022)
The COVID-19 pandemic to date has caused disturbances in all sectors, especially the education sector, which requires learning to be done online. This is the basis of this research. The purpose of this study was to collect information related to creativity and teacher initiatives in developing the quality of online learning during this pandemic. The method used in this research is qualitative with a case study approach. The research was conducted in Sleman. The teachers in this study were four teachers who taught at TahfidzQu Junior High School Sleman. Data collection techniques in this study used structured interviews and documentation review. This research procedure uses the Miles & Huberman model, starting with data collection, data presentation, data reduction, and drawing conclusions. The results of this study include 1) Preparation, implementation and evaluation of online learning is done by making lesson plans with essential materials made into power points and combined with current technology, the assessment is carried out with reference to basic competencies. 2) Utilization of learning platforms, namely google classroom, zoom meet, google meet and Whatsapp group. 3) the role of parents by ensuring the readiness and supervision of their children's learning and communicating with teachers regarding their children's learning development